Silicon‐Stereogenic Monohydrosilane: Synthesis and Applications - Wu, Yichen; Wang, Peng (Angewandte Chemie International Edition, 2022)
Optically active organosilanes have been demonstrated to be versatile chiral reagents in synthetic chemistry since the early seminal contributions by Sommer and Corriu. Among these silicon‐containing chiral architectures, monohydrosilanes, which bear a Si−H bond, hold a unique position because of their facile transformations through stereospecific Si–carbon or Si–heteroatom bond‐formation reactions. In addition, those compounds have also been leveraged as chiral reagents for alcohol resolution, chiral auxiliaries, mechanistic probes, as well as potential optoelectronic materials. This Minireview comprehensively summarizes the synthesis and synthetic applications of silicon‐stereogenic monohydrosilanes, particularly the advances in the transition‐metal‐catalyzed asymmetric synthesis of this class of functional molecules. Monohydrosilanes, which bear a Si−H bond, have been widely leveraged as chiral reagents for alcohol resolution, chiral auxiliaries, mechanistic probes, as well as potential optoelectronic materials. This Minireview comprehensively summarizes the synthesis and synthetic applications of silicon‐stereogenic monohydrosilanes, particularly the advances in transition‐metal‐catalyzed asymmetric synthesis.